Menstrual cycle on internal and external load in amateur women CrossFit players - Cristian Yanez; Diego Calderon; Jose David Peralta; German Jimenez; Oscar Henriquez; Liliana Vergara; Julio Angulo; Nestor Ochoa (CV. FOUNDAE, 2026)
Background: Female physical performance can be influenced by perceived, physiological, and physical factors, making it an important field for further research. Aims: The purpose of this study was to analyze the effects of the menstrual cycle (MC) on the cardiovascular and neuromuscular load of amateur women athletes in CrossFit® during real training situations. Methods: Resistance-trained CrossFit® athletes (without oral contraception) and eumenorrheic women participated in this study (age: 29.6 ± 4.06 years; height: 1.59.3 ± 0.06 m; body mass: 61.22 ± 4.59 kg). A cross-sectional, descriptive study was conducted to evaluate heart rate variability (rMSSD), upper-body strength, muscular endurance, and power performance. The data were analyzed using a one-way repeated-measures ANOVA and the nonparametric Friedman test to assess significant differences among the follicular, ovulatory, and luteal phases for all assessments. The significance was set at p ≤ 0.05. Result: Results revealed no significant differences between the menstrual cycle phases in performance: (HRV RMSSD: H: 0.830, p: 0.443, η2: 0.038), (Push up test: H: 0.041, p: 0.959, η2: 0.002), (countermovement jump: H: 11.921, p: 0.050, η2: 0.362), (rate force development CMJ: H: 1.242, p: 0.299, η2: 0.056), (squat jump: H: 0.439, p: 0.648, η2: 0.020), (rate force development SJ: H: 1.703, p: 0.194, η2: 0.075), (isometric mid-thigh pull: H: 0.019, p: 0.981, η2: 9.132x10-4). Performance is not altered during the MC in female CrossFit® trained athletes. Conclusion: These findings demonstrate that the menstrual cycle does not significantly influence internal and external training load, heart rate variability, or strength and power performance in this population.